Significance and mechanisms of perineural invasion in malignant tumors - Wang, Mengyao; Pu, Niu; Bo, Xitong; Chen, Fuxiang; Zhou, Yilong; Cheng, Qiong (Frontiers in Oncology, 2025)
Cancer remains the second leading cause of death worldwide. Tumor invasion and metastasis pose significant challenges for clinical management. In addition to the traditional pathways of metastasis such as hematologic or lymphatic transmission, perineural invasion (PNI) has become a unique mechanism of metastasis, which is closely associated with neuropathic pain, motor deficits, and poor prognosis. PNI is often observed in malignant tumors of the pancreas, head and neck, gastrointestinal tract, and lungs, and it reflects a unique neurotropic transfer behavior utilizing neural networks. Despite its clinical significance, targeted therapies for PNI are still lacking. This review synthesizes current evidences regarding PNI, elucidates the clinical significance of PNI in tumor metastasis, prognosis, and neurological dysfunction. By integrating the latest advances in multi-omics, we analyzed the potential key molecular pathways and tumor microenvironment drivers of PNI, and proposed future research directions for developing PNI-specific therapies to improve patient outcomes.